Manure amendment acts as a recommended fertilization for improving carbon sequestration efficiency in soils of typical drylands of China - Liang, Shuo; Sun, Nan; Wang, Shuhui; Colinet, Gilles; Longdoz, Bernard; Meersmans, Jeroen; Wu, Lianhai; Xu, Minggang (Frontiers in Environmental Science, 2023)
It is generally known that soil organic carbon (SOC) stocks tend to increase with increasing C input, whereas the C sequestration efficiency (CSE), i.e. the conversion ratio of C input to SOC, differs depending on the amount and type of C input. However, there still exists the need to better understand the impact of various fertilization practices on CSE. We studied the data from 8 long-term experiments located in the main dryland region of China in order to comprehensively assess the key drivers of CSE in the plough layer considering nearly four decades of various fertilizer treatments, i.e. no fertilizer (CK), chemical nitrogen, phosphorus and potassium (NPK/NP), chemical fertilizers plus manure (NPKM/NPM/NM) and straw (NPKS/NPS/NS). Our results showed that manure amendment had the most significant fertilization effect on SOC sequestration with the average CSE of 14.9%, which was significantly higher than that of chemical fertilizations (9.0%) and straw return treatments (7.9%). And manure amendment also had the highest average SOC increase rate of 684 kg C ha-1 yr-1. Variance partitioning analysis (VPA) illustrated that CSE of the main dryland region of China was mostly controlled by edaphic characteristics (32.2%), especially the soil C/N ratio and clay content. The VPA and structural equation modeling (SEM) revealed that the magnitude and influencing factors driving CSE varied among different fertilizer treatments. Soil total N was the limiting factor for CSE in the CK treatment, whereas the soil C/N ratio and pH were the main explanatory factors for CSE in the long-term chemical NPK fertilizer treatment. The negative impact of C input from straw was the main driver of CSE under straw return treatments, though C input had a positive effect on soil physical properties improvement. However, when considering manure amendments, the improvement of soil nutrients and clay content controlled CSE, underlining the main positive direct effect of soil chemical properties. In a nutshell, our results recommend manure plus chemical fertilizers as a sustainable practice for improving C sequestration rate and efficiency in dryland cropping systems.